Strengthening Corporate Governance to Enhance Carbon Emission Disclosure: Evidence from Indonesian Listed Companies - Rangkuti, Maryam Monika; Pasaribu, Asmara Wildani; Rahma, Raudatur (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
In recent years, increasing global attention to climate change and environmental accountability has driven companies, including those in Indonesia, to enhance transparency through carbon emission disclosure as part of their corporate governance practices. This study investigates the influence of corporate governance in enhancing carbon emission disclosure among Indonesian listed companies. Grounded in legitimacy and stakeholder theory, the study examines whether shareholder pressure moderates the governance–disclosure relationship. Using panel data from 33 firms over the 2021–2023 period (99 firm-year observations), this research applies a Random Effect Model (REM) regression approach with company size and profitability as control variables. The results indicate that corporate governance has a positive and significant impact on carbon emission disclosure, suggesting that good governance promotes transparency and accountability in environmental performance. However, shareholder pressure weakens this relationship, implying that excessive financial performance pressure can reduce the effectiveness of governance systems in supporting sustainability transparency. These findings highlight the importance of aligning governance mechanisms with long-term sustainability goals and strengthening policy frameworks to promote carbon-related disclosure in Indonesia.